STRATEGIC ANALYSIS OF CASH WAQF DEVELOPMENT IN INDONESIA USING THE IFE–EFE MATRIX AND SWOT APPROACH - Rusydiana, Aam; Rahayu, Solihah Sari (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2019)
This study attempts to identify the causes and dominant factors that are obstacles in the development of cash waqf in Indonesia, using the IFE EFE Matrix and SWOT methods, and the solutions offered. Based on the results of IFE analysis, the highest ranking of strengths is the ability of cash waqf in expanding the base of waqf fund sources followed by ease and zero cost of funds. While the ranking of weaknesses is the lack of socialization to the community followed by the lack of professional Nazhir human resources. The results of EFE analysis that the highest ranking of opportunities is the potential of unlimited cash waqf followed by the emergence of many sharia financial institutions and Islamic economics study programs in universities. While the highest ranking of threats, namely the relatively weak political will of authorities, and followed by the majority of traditional Nazhirs. It is expected that there will be a joint commitment from various parties, both from policy makers and academics and practitioners to support and encourage efforts to develop the Islamic (social) finance industry, especially in this case the development of cash waqf in Indonesia. Keywords: Cash Waqf, Indonesia, IFE-EFE Matrix, Strategic Management